Hubungan Pemberian ASI Eksklusif dan Konsumsi Zat Gizi Mikro Dengan Kejadian Stunting Pada Balita - Mantri, Kadek Ambara Sidi; Gumala, Ni Made Yuni; Suarjana, I Made (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Stunting is a nutritional status based showed by length for age where in the anthropometric standard assesses nutritional status of children, the measurement results are in the range (z-score) -2 SD up to -3 SD (stunted) and -3 SD (severely stunted). This study aims to determine the correlation between exclusive breastmilk practice and consumption of micronutrient with stunting incident in toddler. This research in an observational study with cross sectional design conducted on 45 toddler, with aged arrange 6 – 24 months. Data on consumption were collected using 24 hours recall as many as two times on different days. Exclusive breastmilk practice data, subject and respondent identity were acquired using questionnaire. Degrees of stunting are expressed by length for age z-score. Data analysis was performed using univariate, bivariate analysis using Spearman and Pearson Correlation test. Based on analysis using Spearman and Pearson Correlation shows that there is no relationship between exclusive breastmilk with the incidence of stunting, there is no correlation between the level of iron consumption with incidence of stunting, and there is no correlation between zinc with incidence of stunting. With regard, it is recommended to provide nutritional education effectively to mothers of toddler to increase knowledge about exclusive breastmilk and micronutrients for prevention of stunting.Keywords: Stunting, Exclusive Breastmilk, Micronutrient